A rich TILLING resource for studying gene function in Brassica rapa - Stephenson, Pauline (BioMed Central, 2010)
BACKGROUND: The Brassicaceae family includes the model plant Arabidopsis thaliana as well as a number of agronomically important species such as oilseed crops (in particular Brassica napus, B. juncea and B. rapa) and vegetables (eg. B. rapa and B. oleracea). Separated by only 10-20 million years, Brassica species and Arabidopsis thaliana are closely related, and it is expected that knowledge obtained relating to Arabidopsis growth and development can be translated into Brassicas for crop improvement. Moreover, certain aspects of plant development are sufficiently different between Brassica and Arabidopsis to warrant studies to be carried out directly in the crop species. However, mutating individual genes in the amphidiploid Brassicas such as B. napus and B. juncea may, on the other hand, not give rise to expected phenotypes as the genomes of these species can contain up to six orthologues per single-copy Arabidopsis gene. In order to elucidate and possibly exploit the function of redundant genes for oilseed rape crop improvement, it may therefore be more efficient to study the effects in one of the diploid Brassica species such as B. rapa. Moreover, the ongoing sequencing of the B. rapa genome makes this species a highly attractive model for Brassica research and genetic resource development. RESULTS: Seeds from the diploid Brassica A genome species, B. rapa were treated with ethyl methane sulfonate (EMS) to produce a TILLING (Targeting Induced Local Lesions In Genomes) population for reverse genetics studies. We used the B. rapa genotype, R-o-18, which has a similar developmental ontogeny to an oilseed rape crop. Hence this resource is expected to be well suited for studying traits with relevance to yield and quality of oilseed rape. DNA was isolated from a total of 9,216 M(2 )plants and pooled to form the basis of the TILLING platform. Analysis of six genes revealed a high level of mutations with a density of about one per 60 kb. This analysis also demonstrated that screening a 1 kb amplicon in just one third of the population (3072 M(2 )plants) will provide an average of 68 mutations and a 97% probability of obtaining a stop-codon mutation resulting in a truncated protein. We furthermore calculated that each plant contains on average ~10,000 mutations and due to the large number of plants, it is predicted that mutations in approximately half of the GC base pairs in the genome exist within this population. CONCLUSIONS: We have developed the first EMS TILLING resource in the diploid Brassica species, B. rapa. The mutation density in this population is ~1 per 60 kb, which makes it the most densely mutated diploid organism for which a TILLING population has been published. This resource is publicly available through the RevGenUK reverse genetics platform http://revgenuk.jic.ac.uk.